New Data on the Middle Paleolithic Site Chelyuskinets II (Based on 2024 Fieldwork Results) - Aleksander K. Otcherednoy; Stanislav O. Remizov; Yaroslav D. Ivanov; Vasilisa S. Smolkina; Ekaterina M. Kezina; Redzhep N. Kurbanov; Idris A. Idrisov (Нижневолжский археологический вестник)
The article presents the results of field work of the Lower Volga Paleolithic Expedition of the Institute of Archaeology and Ethnography of the Russian Academy of Sciences, Siberian Branch, organized within the framework of the integrated Lower Volga expedition of the Institute for the History of Material Cultures of the Russian Academy of Sciences in 2024. During the season, the study of the Middle Paleolithic site Chelyuskinets II, located in the Pichuga gully of the Dubovsky area of the Volgograd region, was continued. The work of 2024 was aimed at studying the chronostratigraphic position of two Cultural Horizons discovered in the previous year in a new section of the site, as well as clarifying the area of their distribution.